Public management reform under the dome of accruals (Presidential Decree 54/2018): Investigation of the effects on the financial information and the audit of the General Government entities - Goumas, Spyridon; Karastogiannis, Pavlos (International Conference on Business and Economics - Hellenic Open University, 2023)
Presidential Decree 54/2018 legislated the introduction of accrual basis accounting from 1/1/2023 to all entities of the General Government of Greece in accordance with the European System of Accounts 2010. We study the effect of accrual basis accounting under the 54/2018 on financial information and audit of entities, as well as the transition process. The research was conducted using the qualitative method, the structured interview protocol was the data collection tool and the participants were the employees of the Third Department of the General Government Accounting Plan. We find that there will be objective information of the entity's financial position and performance, depreciation, provisions, impairments and fair value of assets. Transparency and accountability are strengthened, audits are facilitated to establish useful sound financial management, there is a central control of public finances and the phenomena of corruption and financing of public officials will be reduced. The job of the audit mechanisms is strengthened, audits become more effective and the way available resources are managed is more precisely controlled. Major difficulties during the transition are the lack of personnel and an appropriate accounting information system, and in combination with the covid-19 pandemic, it was noted that the transition cannot be implemented on 1/1/2023 and for that reason our results suggest an extension to 2025 for the transition, proposal which was implemented on July 30, 2022 with Law 4964/2022. EL Classifications: H83, P41, M48. Key words: Accrual Accounting, Accounting Reform, General Government, Accountability, Audit.